Analisis Rasio Keuangan Untuk Mengukur Kinerja Keuangan Atas Penyaluran Kredit PT. Bank Neo Commerce Tbk. - Muhammad An Nafi Alfarizi; Rola Manjaleni (Jurnal Ilmiah Manajemen, Ekonomi dan Akuntansi, 2025)
. This study aims to analyze financial ratios in assessing the financial performance of credit distribution at PT. Bank Neo Commerce Tbk. during the 2019-2023. The research method used is descriptive quantitative, utilizing secondary data in the form of annual financial statements. The financial ratios analyzed include Loan to Deposit Ratio (LDR), Capital Adequancy Ratio (CAR), Return on Assets (ROA), Net Interest Margin (NIM), Operating Expenses to Operating Income (BOPO), Non-Performing Loan (NPL). The results show that LDR and CAR are categorized as healthy to very healthy. Meanwhile, ROA and BOPO are in an unhealthy category, reflecting low efficiency and profitability. NIM and NPL show very healthy performance, indicating effective credit management and strong interst margins. This research provides a comprehensive overview of the bank’s credit distribution and financial performance over the past five years.